Frequência do Alelo HLA-DRB1 em portadores de anemia falciforme atendidos na Fundação Hospitalar de Hematologia e Hemoterapia do Amazonas - Sampaio , Giselle Moreira (2020)
Sickle cell anemia (AF) is one of the genetic diseases of greatest epidemiological relevance determined by a point mutation in the beta gene of the globin chain, resulting in a variant hemoglobin causing numerous complications. Although transfusion therapy is used as a therapeutic modality, there is a risk of the formation of antibodies against blood group antigens, leading to difficulties in the search for compatible blood for patients with SCA. The human leukocyte antigen (HLA), responsible for encoding surface proteins that recognize and present antigens, have alleles and haplotypes that can predispose or protect the appearance of clinical manifestations acting as genetic markers. Objective: Thus, our objective was to determine the frequency of HLA-DRB1 antigens in patients with sickle cell anemia treated at the Fundação Hospitalar de Hematologia e Hemoterapia do Amazonas - FHEMOAM. Material and Methods: A cross-sectional descriptive study was carried out with 109 DNA samples from patients with FA. Genotyping was performed using the PCR-SSO method for the DR locus of the HLA class II system using the LABTypeTM SSO Class II DRB1 Kit (One Lambda) with Luminex technology. The determination of the genotype and allele frequencies of the HLA systems and blood groups was performed by direct counting with absolute (n) and relative (%) frequencies, and the numerical variables were analyzed using position and dispersion measures. Results: There was a predominance of females (56.9%) and of the self-declared browns (88.1%), the age range ranged from 1 to 52 years. A percentage of alloimmunized patients was 10% and the erythrocyte antigens corresponding to the Rhesus, Kell and Diego systems. 13 specificities were identified for the HLA alleles, the HLA-DRB1 * 04 (19.3%), -DRB1 * 3 (10.6%) and -DRB1 * 16 (10.1%) alleles being more representative in patients. Conclusion: the HLA typing of patients corresponds to that found in other regions, confirming the susceptibility of the HLA-DRB1 * 04 allele to the formation of alloantibodies